PENGARUH PROKRASTINASI AKADEMIK TERHADAP TINGKAT STRES AKADEMIK MAHASISWA TADRIS MATEMATIKA UIN K.H ABDURRAHMAN WAHID PEKALONGAN - Soleha Oktaviani; Zahra Aulia; Muthia Isna Arofah; Nalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic procrastination is a common behavior among university students characterized by delaying the completion of academic tasks, which may adversely affect their psychological well-being, particularly academic stress. Although numerous studies have examined the relationship between academic procrastination and academic stress, the findings remain inconsistent, indicating the need for further investigation in different educational contexts and student populations. This study aimed to examine the effect of academic procrastination on the academic stress levels of students in the Mathematics Education Study Program at UIN K.H. Abdurrahman Wahid Pekalongan. This research employed a quantitative approach using a survey design. The sample consisted of 40 students selected through a convenience sampling technique. Data were collected using Likert-scale questionnaires measuring academic procrastination and academic stress. The collected data were analyzed using simple linear regression with the assistance of SPSS software. The results revealed that the significance value was 0.773, which exceeded the significance level of 0.05, while the calculated t value (0.290) was lower than the critical t value (2.024). These findings indicate that academic procrastination does not have a statistically significant effect on the academic stress levels of Mathematics Education students at UIN K.H. Abdurrahman Wahid Pekalongan. The findings further suggest that academic stress is influenced not only by academic procrastination but also by other factors, including time management skills, coping strategies, learning motivation, social support, and individual characteristics. Therefore, efforts to reduce academic stress should adopt a comprehensive approach by considering the multiple factors that contribute to students' psychological well-being.